Comparison of two measures of behavior change in children after day surgery. Issue 1 (10th November 2021) - Lee‐Archer, Paul F; Gibbons, Kristen; Reade, Michael; von Ungern‐Sternberg, Britta S; Long, Deborah
Abstract: Background: A contemporary, well‐validated instrument for the measurement of behavior change in children after general anesthesia is lacking. The Post Hospitalization Behavior Questionnaire for Ambulatory Surgery (PHBQ‐AS) has been developed as an updated version of the original Post Hospitalization Behavior Questionnaire (PHBQ) to better reflect the current patient population and modern anesthetic practices. Aims: To assess the reliability of the PHBQ‐AS and determine concurrent validity with another measure of child behavior, the Strength and Difficulties Questionnaire (SDQ). Methods: We compared the PHBQ‐AS with the SDQ in 248 children presenting for day‐case surgery. A baseline SDQ measurement was taken prior to surgery, and then, both scales were administered on days 3, 14, and 28 postsurgery. Results: The PHBQ‐AS demonstrated good reliability in terms of internal consistency with a Cronbach's alpha of 0.79 and split‐half correlation with Spearman Brown adjustment of 0.85. There was weak correlation with the SDQ on day 3 postoperatively (Pearson's r  = 0.201), moderate correlation on day 14 (Pearson's r  = 0.421), and weak‐to‐moderate correlation on day 28 (Pearson's r  = 0.340). A cut‐off score of 3.2 on the PHBQ‐AS for the diagnosis of negative behavior demonstrated equivalence with the SDQ results; however, the SDQ results remained relatively constant throughout the study period and reflected the expected rate of increased risk of problem behavior in children. Conclusions: The PHBQ‐AS showed good reliability but only had weak‐to‐moderate correlation with another measure of child behavior, the SDQ. Further validation is required before the PHBQ‐AS is used for the routine measurement of behavior change in children after anesthesia, or alternatively, a new instrument needs to be developed in order for research to advance in this area.